Zoledronate in the prevention of Paget's (ZiPP): protocol for a randomised trial of genetic testing and targeted zoledronic acid therapy to prevent SQSTM1-mediated Paget's disease of bone. Issue 9 (4th September 2019) - Cronin, Owen; Forsyth, Laura; Goodman, Kirsteen; Lewis, Steff C; Keerie, Catriona; Walker, Allan; Porteous, Mary; Cetnarskyj, Roseanne; Ranganath, Lakshminarayan R; Selby, Peter L; Hampson, Geeta; Chandra, Rama; et al.
Abstract : Introduction: Paget's disease of bone (PDB) is characterised by increased and disorganised bone remodelling affecting one or more skeletal sites. Complications include bone pain, deformity, deafness and pathological fractures. Mutations in sequestosome-1 ( SQSTM1 ) are strongly associated with the development of PDB. Bisphosphonate therapy can improve bone pain in PDB, but there is no evidence that treatment alters the natural history of PDB or prevents complications. The Zoledronate in the Prevention of Paget's disease trial (ZiPP) will determine if prophylactic therapy with the bisphosphonate zoledronic acid (ZA) can delay or prevent the development of PDB in people who carry SQSTM1 mutations. Methods and analysis: People with a family history of PDB aged >30 years who test positive for SQSTM1 mutations are eligible to take part. At the baseline visit, participants will be screened for the presence of bone lesions by radionuclide bone scan. Biochemical markers of bone turnover will be measured and questionnaires completed to assess pain, health-related quality of life (HRQoL), anxiety and depression. Participants will be randomised to receive a single intravenous infusion of 5 mg ZA or placebo and followed up annually for between 4 and 8 years at which point baseline assessments will be repeated. The primary endpoint will be new bone lesions assessed by radionuclide bone scan. Secondary endpoints will include changes in biochemical markers of bone turnover, pain, HRQoL, anxiety, depression and PDB-related skeletal events. Ethics and dissemination: The study was approved by the Fife and Forth Valley Research Ethics Committee on 22 December 2008 (08/S0501/84). Following completion of the trial, a manuscript will be submitted to a peer-reviewed journal. The results of this trial will inform clinical practice by determining if early intervention with ZA in presymptomatic individuals with SQSTM1 mutations can prevent or slow the development of bone lesions with an adverse event profile that is acceptable. Trial registration number: ISRCTN11616770